Transitional justice and conflict transformation: a tenable nexus? the case of South Africa's Truth and Reconciliation Commission - Kisiangani, Emmanuel Nalianya (My University, 2009)
Abstract The South African Truth and Reconciliation Commission (TRC) has been widely hailed as unprecedented and exemplary. It has motivated efforts to establish truth commissions in various other parts of the world. Inherent in the normative treatment of the South African TRC as a paradigm to be followed, is the assumed correlation between its objectives and those of conflict transformation. This assumption, while prominent in a number of contexts especially outside South Africa, has often passed with little interrogation. The primary aim of this study is to assess the assumed correlation by formulating the South African TRC within conflict transformation theory. A secondary goal which should be seen in context of the study’s primary objective is to assess whether the South African TRC constitutes a paradigm to be followed by other relevant contexts. The research philosophy and methodology deemed appropriate for the study is the reflective mode of inquiry which is once in a while supplemented by primary data. The aim is to delineate the instrumental and practical value of those constructs that treat the South African TRC as a transformative framework. Eventually the study substantiates these assertions and makes analytical judgments on the relationship between the TRC and conflict transformation. The broad conclusion of the study is that the biggest role played by the South African TRC was to engage the society in discourse with its past. It symbolically underscored the need to build right relationships and social structures that promote peace and the rule of law. The study, however, argues that the exercise of engaging in constructive relational and structural change needed to transcend symbolism and address the underlying structures and human relationships at various levels, politically, socially and economically. Other than making recommendations, the long term relational and structural transformation was well beyond the TRC’s mandate. On the tendency of other countries to treat the South African TRC as the standard practice and paradigm to be borrowed, the study maintains that the TRC may have been unique and anomalous with its provision for conditional amnesty and public hearings, but it sometimes inappropriately skews the views of many in other distinctively different contexts, in a way that needs to be reconsidered.